Effects of green coffee extract supplementation on blood pressure and antioxidants status in patients with non-alcoholic fatty liver disease - Hosseinabadi, Samaneh; Rafraf, Maryam; Asghari-Jafarabadi, Mohammad (Progress in Nutrition, 2020)
Background and aim: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disorder. Hypertension and increased oxidative stress are important risk factors for NAFLD and its complications such as cardiovascular disease. This study aimed at assessing the effects of green coffee extract (GCE) on blood pressure (BP) and antioxidants status in patients with NAFLD. Methods: This double-blind, randomized, controlled clinical trial was conducted on 44 individuals with NAFLD aged 20-60 for male & 20-50 years for females and body mass index (BMI) ranged 25 - 34.99 kg/m2. The intervention group (n=21) consumed GCE capsules (200 mg) two time per day for 8 weeks. The control group (n=23) received two placebo capsules daily for the same period. Anthropometric and BP measurements, dietary intakes, physical activity levels, ultrasonography and fasting blood samples were collected at the baseline and at the end of the trial. Data were analyzed by independent t test, paired t test and analysis of covariance. Results: GCE supplementation significantly reduced systolic BP (SBP) (mean difference = -9.62 and 95% confidence interval = -14.98 to -4.26), and BMI of subjects compared to control group at the end of study. Diastolic BP decreased significantly within GCE group and serum MDA increased within control group after intervention compared to their baseline measurements (P < 0.05). Changes in total anti-oxidant capacity were not significant in any of groups. Conclusion: GCE supplementation improved SBP and BMI in NAFLD patients. Further studies are warranted to evaluate more effects of GCE on NAFLD management.